Cross-comparison of microbiota in the oropharynx, hypopharyngeal squamous cell carcinoma and their adjacent tissues through quantitative microbiome profiling - Hui-Ching Lau; Yujie Shen; Huiying Huang; Xiaohui Yuan; Mengyou Ji; Hongli Gong; Chi-Yao Hsueh; Liang Zhou (Journal of Oral Microbiology, 2022)
Aims To clarify the absolute abundance of microbial communities on hypopharyngeal squamous cell carcinoma and their correlation to those in the oropharynx.Methods Clinical data, swabs, and tissue samples from 27 HPSCC patients were collected in this study and divided into three sampling groups: 19 oropharyngeal mucosa (OPM), 27 hypopharyngeal carcinomas tissues (HC), and 26 corresponding adjacent tissues (AT). Relative microbiome profiling (RMP), and quantitative microbiome profiling (QMP) of 16S rRNA amplicon sequencing were used for analysis.Results Beta-diversity showed that abundance and phylogenetic tree in OPM group were less when compared to either HC and AT. Although HC and AT were found to have similar microbiota, Bray-Curtis based beta-diversity still highlighted differences. Fusobacterium, Porphyromonas, Haemophilus, and Peptostreptococcus at the genus level in OPM were positively correlated with HC. After categorizing HC through TNM staging, the abundance of genera Fusobacterium, Parvimonas, and Dialister were found to be enhanced in higher T classifications (T3-4) and advanced stages (Ⅳ).Conclusions QMP yielded more comprehensive results than RMP. Dysbiosis was found in OPM groups and could be used to narrow down differential microbiome for the HC group. Genera of Parvimonas, Fusobacterium, and Dialister were deemed as risk factors of advanced HPSCC.